The killer shrews - Kellogg, Ray, -1976; Simms, Jay; Best, James, 1926-2015; Hollywood Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Hollywood Pictures Corp., 1959)
A scientist on an island is working on a project, to help with the world population problem, accidentally creates giant shrews that escape his lab and devour every animal on the island. With nothing else to eat, the giant shrews set their sights on the compound of scientists and their guests. Led by Captain Thorne Sherman (James Best), the group must make a break for his ship to escape from the ravenous shrews.
Originally released as a motion picture in 1959.
James Best, Ingrid Goude, Ken Curtis, Gordon McLendon, Baruch Lumet, Judge Henry Dupree, Alfredo DeSoto.
Cinematographer, Wilfrid M. Cline; editor, Aaron Stell; music composed by Harry Bluestone and Emil Cadkin; music editor, Gil Marshand.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 5, 2016).
Keywords: Southern short-tailed shrew -- Drama; Scientists -- Drama; Overpopulation -- Drama; Genetic engineering -- Drama; Hurricanes -- Drama; Drums (Containers) -- Drama; Dallas (Tex.); Monster films; Science fiction films; Feature films; Horror films; Internet videos; Streaming video